Higher spin AdS3 holography with extended supersymmetry - Creutzig, Thomas; Hikida, Yasuaki; Rønne, Peter B. (Journal of High Energy Physics, 2014)
Abstract: We propose a holographic duality between a higher spin AdS3 gravity with so(p) extended supersymmetry and a large N limit of a 2-dimensional Grassmannian-like model with a specific critical level k = N and a non-diagonal modular invariant. As evidence, we show the match of one-loop partition functions. Moreover, we construct symmetry generators of the coset model for low spins which are dual to gauge fields in the supergravity. Further, we discuss a possible relation to superstring theory by noticing an N = 3 supersymmetry of critical level model at finite k, N. In particular, we examine BPS states and marginal deformations. Inspired by the supergravity side, we also propose and test another large N CFT dual obtained as a Z2 automorphism truncation of a similar coset model, but at a non-critical level.
CRIS-Team Scopus Importer:2024-06-24
Keywords: AdS-CFT Correspondence; Conformal and W Symmetry; Extended Supersymmetry; Higher Spin Gravity